Molecular profiling of individual FDA-approved clinical drugs identifies modulators of nonsense-mediated mRNA decay - Jingrong Zhao; Zhelin Li; Ruchira Puri; Kelvin Liu; Israel Nunez; Liang Chen; Sika Zheng (Elsevier, 2022)
Nonsense-mediated mRNA decay (NMD) degrades transcripts with premature stop codons. Given the prevalence of nonsense single nucleotide polymorphisms (SNPs) in the general population, it is urgent to catalog the effects of clinically approved drugs on NMD activity: any interference could alter the expression of nonsense SNPs, inadvertently inducing adverse effects. This risk is higher for patients with disease-causing nonsense mutations or an illness linked to dysregulated nonsense transcripts. On the other hand, hundreds of disorders are affected by cellular NMD efficiency and may benefit from NMD-modulatory drugs. Here, we profiled individual FDA-approved drugs for their impact on cellular NMD efficiency using a sensitive method that directly probes multiple endogenous NMD targets for a robust readout of NMD modulation. We found most FDA-approved drugs cause unremarkable effects on NMD, while many elicit clear transcriptional responses. Besides several potential mild NMD modulators, the anticancer drug homoharringtonine (HHT or omacetaxine mepesuccinate) consistently upregulates various endogenous NMD substrates in a dose-dependent manner in multiple cell types. We further showed translation inhibition mediates HHT's NMD effect. In summary, many FDA drugs induce transcriptional changes, and a few impact global NMD, and direct measurement of endogenous NMD substrate expression is robust to monitor cellular NMD.